Numerical simulation of the air flow in an intake flange of a competition vehicle - Tolentino Masgo, San Luis Baudilio (2020)
The intake flange is a mechanical device that restricts the amount of mass air flow to be injected into the engine cylinder, and is used in racing vehicles. In the present work, the air flow is simulated in a 2D computational domain with axial symmetry for the geometry of a convergent-divergent intake flange, in order to determine the variations of the thermodynamic parameters of the flow field. For the simulation of the flow, the ANSYS-Fluent code that uses the finite volume method was used. The governing equations were used for compressible flow: mass equation, amount of movement, energy and state; in addition, Menter’s SST   turbulence model was used. The results of the density, velocity, pressure and temperature flow field, as well as the Mach number, for six pressure ratios, show variations in thermodynamic quantities in different regions of the domain, before and after the shock wave; as well as the regions where separation and recirculation of the flow occurs in the adjacencies of the divergent wall. It is concluded that, when the shock occurs, the curvature of the wall of the divergent section contributes to the detachment of the boundary layer, cuasing transition in the flow development. In addition, for the outlet pressure of , the flow reaches a máximum value of Mach 1.8, and temperature of  180 K (-93 ºC); and at the outlet of the flange the flow reaches a lower value of Mach 1.